新型高效綠能薄膜矽鍺太陽電池之研發( I ) - 張俊彥; CHANG CHUN-YEN (My University, 2011)
本研究主要訴求為改善產業界現行的太陽能電池製程方法，以達到可以直接將研究 成果運用在產業界製造過程上，達到環保、高效率、低成本的目標。 圖一為堆疊型矽薄膜太陽能電池之結構圖與堆疊型矽薄膜太陽能電池之能帶結構 圖，然而在不改變傳統太陽能能帶結構的情況之下，要達到與現行普及的發電機制同樣 的成本是極為不可能的。而本研究方向由張俊彥教授針對此點提出各種改善現行堆疊型 矽薄膜太陽能電池能帶結構之方法，以「非晶/微晶矽薄膜結晶率」、「奈米點」、「非晶/ 微晶矽鍺薄膜加入氧、碳等原子」、「非晶/微晶矽薄膜加入氧、碳等原子」、「非晶/微晶 矽鍺薄膜」、「超晶格薄膜」加以控制其能帶結構，針對所提出的數種方法研究其物理原 理、薄膜光特性、電特性、及製程方法並在大面積量產線上實驗其可行性，再以各種量 測實驗驗證，並改善傳統結構，以期達到提高效率、降低成本之目的，使太陽能電池可 以成為未來發電主力，取代現行的發電機制，使地球環境得以救贖。 本研究發現數種提高短路電流、開路電壓、填充因子、轉換效率的方法與能帶結構： 在本質吸光層中以「能帶漸變結構」使電子或電洞在傳輸上更為有效率，可使填充因子 增加；在各處界面上使能帶以結構漸變方式，減少其載子復合機率、增加其填充因子； 以「漸變能帶結構工程」更可有效使光子在元件結構中適當的位置被吸收而產生電子電 洞對，減少產生的載子轉換為散亂無用的熱能而導致太陽能電池轉換效率大幅低於物理 極限的轉換效率。 第一年的研究計畫至今不但達到計畫大多數的目標，並將由張俊彥教授提出的觀念 與物理應用在現行太陽能廠的生產過程中，成果中轉換效率可以達到轉換效率11.7% 的 世界水準。

This study aims on improving the current manufacturing method in the industry directly. The goal what we pursue is applying the results of this research to not only the industrial manufacture process, but also to the achievement of the environmental protection, high efficiency, and low cost. Figure.1: The device structure and energy-band structure of traditional, mass-productive silicon thin-film tandem solar cell. Figure.1 depict out the device structure and the energy-band structure of traditional, mass-productive silicon thin-film tandem solar cells respectively. Such specific kind of silicon thin-film tandem solar cell strongly dominates the solar-cell industry currently. Unfortunately, without modifying the energy-band structure of these cells, it is almost impossible to cut the cost of solar electricity down to the level of that of fossil-fuel electricity. With focus on the energy-band structure of traditional silicon thin-film tandem solar cells, Professor Chun-Yen Chang proposed several methods and techniques including “tuning the crystallization rate of amorphous/microcrystalline silicon thin-films”, “adding of nano-dots”, “introducing amorphous/microcrystalline silicon or silicon-germanium thin-films”, “introducing carbon or oxygen atoms into the amorphous/microcrystalline silicon or silicon-germanium thin-films”, and the insertion of “superlattices” to control and modify the energy-band structures. We were involved in investigating the physical principles, the optical and electrical properties of the thin film and the optimization of fabrication methods. All the cells were demonstrated on the mass-productive fabrication-lines with large device area. Furthermore, via various measurement techniques and characteristics, the goals of efficiency escalation and cost reduction are achievable. Eventually, silicon solar cells will be the mainstream of electric power and replace traditional fossil-fuel electricity. Redeeming our earth from planet-warming greenhouse gases is highly expected. In this research, several techniques and energy-band structures had been found to get an escalation in short-circuit current (Isc), open-circuit voltage (Voc), fill-factor (FF) and the efficiency. First the introduction of graded energy-band profiles in the intrinsic absorbing layer to enhance the transport efficiency of electrons or holes. Second via inserting graded energy-band profiles at the heterojunctions, the reduction of recombination rate of carriers is achievable and the fill-factor (FF) can be effectively raised. Besides, the “graded-energy-band-profile engineering” gets the ability to force photons to be absorbed at a suitable position on the energy-band profiles. To summarize, all these techniques are effective in cutting the production of disorderly and useless heat and propelling the efficiency upwardly toward the physical limitations. We have reached most of our expected targets in the first year, and continuously apply our ideas, physical concepts and results to the manufacturing process in current solar cell fabrication industry. Through this process, the efficiency of energy conversion of the demonstrative cell can reach to a world-class 11.7%.
Process of Cost Effective Green Thin Film Si/Ge Solar Cell( II )( III )
Keywords: 矽鍺薄膜太陽能電池; 能帶工程; 光捕捉。